2006
DOI: 10.1080/17470910600976430
|View full text |Cite
|
Sign up to set email alerts
|

Language in shadow

Abstract: The recent finding that Broca's area, the motor center for speech, is activated during action observation lends support to the idea that human language may have evolved from neural substrates already involved in gesture recognition. Although fascinating, this hypothesis can be questioned because while observing actions of others we may evoke some internal, verbal description of the observed scene. Here we present fMRI evidence that the involvement of Broca's area during action observation is genuine. Observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…They further note that the brain substrate for mirror neurons in monkeys is homologous with Broca’s area in humans, a region long known to be involved in language production and understanding in humans. More recent research in neuroscience implicates Broca’s area in action understanding as well (e.g., Fadiga & Craighero, 2006; Fadiga et al, 2006). Communication canonically began face-to-face in small groups.…”
Section: Resultsmentioning
confidence: 99%
“…They further note that the brain substrate for mirror neurons in monkeys is homologous with Broca’s area in humans, a region long known to be involved in language production and understanding in humans. More recent research in neuroscience implicates Broca’s area in action understanding as well (e.g., Fadiga & Craighero, 2006; Fadiga et al, 2006). Communication canonically began face-to-face in small groups.…”
Section: Resultsmentioning
confidence: 99%
“…The comprehension is inherent in the neural organization of the two individuals. Note also that the activation of Broca ' s area during motor act observation is not due to a verbal description of the observed action, but to a real coding of motor act (for evidence on this point, see Fadiga et al, 2006). The mirror neuron system of monkeys is a closed system linked to objects, while, in order to communicate, this system should become an open system, able to describe actions and objects.…”
Section: Languagementioning
confidence: 99%
“…Mirror neurons, instead, fire when the monkey makes a goal-directed action and also when it observes another monkey or an experimenter performing the same or a similar action. Recent studies, mainly based on brain imaging techniques, indicate the existence of both canonical and mirror neurons in humans (Buccino et al, 2001;Grèzes et al, 2003;JohnsonFrey et al, 2003;Fadiga et al, 2006). Using fMRI it has been shown that in humans the observation of both object directed actions and mimed actions leads to activation of different regions in the premotor cortex, including the Broca's region (Buccino et al, 2001) and the parietal cortex (Fogassi, Ferrari, Gesierich, Rozzi, Chersi, & Rizzolatti, 2005).…”
Section: Introductionmentioning
confidence: 99%